Market-oriented job skill valuation with cooperative composition neural network - Ying Sun (Nature Portfolio, 2021)
The value assessment of job skills is critical for companies to select and retain the right talent and for individuals to develop them. Here the authors show that a data-driven method based on an enhanced neural network can assign meaningful value to job skills in a quantitative way and outperforms benchmark models for job salary prediction.